EFFECTIVE METHODS FOR LEARNING ENGLISH EASILY - Umarova Munavvar Nurmuhammedovna; Anorboyeva M. S (TADQIQOTLAR, 2025)
Abstract This article discusses effective and simple methods for learning English. It focuses on techniques that are suitable for beginners and intermediate learners, including interactive learning, technology integration, and daily practice routines.